The Determining Factor of Inconsistencies in French Feminist Foreign Policy in the Field of Protection Against Women’s Violence - Az-zahra, Sheila Salma; Yudono, Raden Maisa; Maliki, Musa; Situmeang, Nurmasari (Journal of Strategic and Global Studies, 2025)
Stratégie internationale de la France pour l'égalité femmes-hommes (2018-2022) is an international strategy on gender promoted by the French Government. It aims to promote the value of gender equality and women's empowerment, especially in protecting women's rights from any acts of violence in the European Union. Unfortunately, the French Government has shown inconsistencies in the implementation of the feminist foreign policy, which has increased the number of violence from the beginning of this policy until nowadays. This research was conceived by a liberal feminism approach and conceptualized under the feminist foreign policy and patriarchy concepts to prove the determining factor of inconsistency in feminist foreign policy that set out in the frame of Stratégie internationale de la France pour l'égalité femmes-hommes (2018-2022). The argument can be proceeded by conducting an explanatory qualitative method. The data research is based on primary and secondary data sources through document studies. This research proved that France's inconsistency of feminist foreign policy is caused by France’s cultural matter of patriarchal values. Patriarchal values can be indicated through five indicators: policy regulations, funding systems, government structures, EU cooperative relations, and actors involved in the policy. As a result, gender-based violence is still very common in society and gender equality is impossible to achieve as long as policies and laws reformed by the government still contain elements of patriarchy.